Zinc-Catalyzed Markovnikov-Type Hydroisothiocyanation of Alkenes with Ammonium Thiocyanate - Taniguchi, Nobukazu (Synlett, 2022)
A ZnI2-catalyzed addition of ammonium thiocyanate to olefins in the presence of 4-toluenesulfonic acid and tetrabutylammonium iodide has been developed. The reaction proceeds by a Markovnikov-type process and a radical isomerization, and gives the corresponding isothiocyanates selectively and in good yields.
Keywords: zinc catalysis; Markovnikov reaction; isothiocyanates; thiocyanates; alkenes; isomerization